HIGH TEMPERATURE ANNEALING INFLUENCE ON ELECTRIC PROPERTIES OF NANOCOMPOSITE (FeCoZr)81.8(CaF2)18.2 - Bondariev, Vitalii; Kołtunowicz, Tomasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
This paper presents results of researches on annealing influence on AC electric properties of nanocomposite (FeCoZr)x(CaF2)(100-x) with metallic phase content x = 81.8 at.% which was produced by ion-beam sputtering in argon Ar and oxygen O2 atmosphere. It was observed that there are two types of potential wells in the material, which are different in relaxation times. Annealing causes maximums disappearance on frequency dependence on frequency coefficient α and growing section smoothing, which means complete oxidation of material.